Model of High Temperature Heat Transfer in Metals (Global Journal of Science Frontier Research, 2017)
Based on the analysis of the atomic – ionic radii and volume characteristics new the approach (exchange – fluctuation) is considered under band blurring. It is shown that atomic space between atomic and ionic radii is divided into the ready Kλ cells (where K - nearest neighbours, λ = h/mc). The heat energy transfer in this space is represented in the model of fluxes, exchanging by the electron density in the ±Kλ mode.
Keywords: ionic and atomic radii; electronic density; fluctuation density